Analysis of Social Media Management Strategies: A Case Study of Bekelir Tourist Village - Messya Sungoro; Budi Setiawan (Politeknik Sahid, 2026)
Bekelir Tourism Village is a community-based destination that has successfully transformed from a slum area into a thematic village with colorful mural identities. However, the number of tourist visits declined in 2021–2024 because social media management was not optimal. The research problem formulation is how the social media condition of Bekelir Tourism Village is and what the management strategy is. This study aims to formulate effective social media management strategies to support sustainable tourism promotion. The research method uses a qualitative approach with techniques such as interviews, observation, documentation, SWOT analysis, and POAC (Planning, Organizing, Actuating, Controlling) strategy implementation. There were 9 respondents in this study. The results show that Bekelir Tourism Village has strengths in the form of unique mural identity, community support, and strategic location, but faces weaknesses in the form of limited human resources and lack of content consistency. The implementation of POAC can be a solution through content planning, team organization, digital training, and continuous promotion monitoring.